Método ISR para la simulación de cascadas de extracción líquido-líquido: un enfoque práctico con MATLAB® (2017)
In the mathematical modeling of liquid-liquid extraction cascades, one of the first approximations corresponds to those followed by the ISR (Isothermal Sum of Rates) method. The present work addresses the assumptions, limitations, advantages and disadvantages of the method, with emphasis on its implementation in the programming language Matlab®. The validation was carried out by simulating an extraction cascade for the separation of a mixture of benzene and heptanes carried out with dimethylformamide (DMF) and water, obtaining an average derivation of less than 5 %.